From powders to freestanding electrodes: Assembly active particles into bacterial cellulose for high performance supercapacitors. (10th August 2021) - Luo, Wanxia; Guo, Nannan; Wang, Luxiang; Cao, Yali; Xu, Mengjiao; Jia, Dianzeng; Feng, Shizhan; Gong, Xinyi; Zhang, Su
Abstract: The assembly of powdered materials into freestanding electrodes can avoid the usage of metallic current collectors and thus reduce the weight and cost of devices. In this work, we prepared robust, binder-free freestanding membrane electrodes consisting of a three-dimensional network of bacterial cellulose (BC) with acetylene black and activated carbon uniformly embedded. Filtration as a facile method was employed to prepare the highly hydrophilic and conductive porous network. This architecture facilitated electrolyte infiltration and significantly enhanced the electrolyte uptake (6 times of the entire electrode weight), which subsequently improved ion transport and reduced the contact resistance between electrode and electrolyte. Owing to the high porosity, excellent wettability and the efficient utilization of active material, the obtained freestanding electrode with a mass loading of 3 mg cm −2 delivered a high capacity of 276 F g −1 at 1 A g −1 . It also exhibited an excellent cycle stability at 5 A g −1 without detectable capacity fading after 10, 000 cycles in a two-electrode system. More importantly, a high specific capacitance of 167 F g −1 at 1 A g −1 and a high energy density of 5.3 W h kg −1 at 163 W kg −1 with respect to the overall weight of electrode were achieved at a commercial level mass loading of 10 mg cm −2, which considerably outperformed common electrode using nickel foam as current collector. This work provided a facile and effective way in producing lightweight, low cost and high-performance electrodes.